Expression of steroidogenic enzymes in placentome of ewes with pregnancy toxemia after two parturition induction methods - Ozalp, G. R.; Ortac, C. T.; Bozkurt, B.; Risvanli, A.; Aktar, A.; Yavuz, A.; Seker, I. (Hellenic Veterinary Medical Soc, 2023)
The regulation pattern of important enzymes in placental steroidogenesis and prostaglandin production in ewes with pregnancy toxemia is reviewed. The alterations of gene expressions after the administration of aglepristone (AG) and dexamethasone (DEX) are also discussed. Four healthy (CG) and 22 ewes with experimental pregnancy toxemia were included in the study. Ewes with pregnancy toxemia of group AG (n=9) and group DEX (n=9) were injected twice with 10 mg/kg of aglepristone and once with 5 ml dexamethasone respectively to induce parturition on 141 & PLUSMN;1,3 day of gestation; whereas healthy control [Group CG (n=4)] and pregnancy toxemia [Group PT (n=4)] group received no treatment for parturition induction. Placentomes were immediately collected right after the expulsion of the last lamb. mRNA extraction from total placentome capsule, cotyledon and caruncle was carried out and Real-Time PCR was performed. Serum samples were collected from ewes and cortisol, PGFM, PGE2, estrone sulfate and progesterone concentrations were measured after treatments until parturition. The lowest mRNA expressions of steroidogenic enzymes were detected in group PT. Interestingly expression pattern of steroidogenic enzymes in group AG was similar to group PT. No difference was found in mRNA expressions of 3 & beta;HSD and CYP19 among groups. Between groups, AG-DEX the mRNA expressions in the caruncle of PTGS2/COX2 and PGFS were statistically different respectively (P<0.005). A significant difference could be observed in EP3 expression in the caruncle of DEX and AG compared to CG (P<0.05); however PTGES, EP1, EP2, and EP4 expressions were not statistically different among groups (P>0,05). Estrone sulfate, PGE,2 and PGFM concentrations were statistically different, however, no difference was observed in cortisol levels between groups. The present study suggests that the endocrinologic pathway controlling parturition is different in ewes with pregnancy toxemia. Dexamethasone administration endocrinologically mimicked normal partu-rition, but the genes regulating uterine contractions were similarly expressed, as in group PT. Probably expressions of EP1 and tissue-specific counter-expressions of cervical EP genes could refer to the pathogenesis of insufficient cervical dilatation, observed in pregnancy toxemia and dexamethasone applications.
Keywords: Prostaglandins; Steroidogenesis; Ewes; Partuririton; Aglepristone; Dexamethasone